The Design Of Mutranesia Application As A Support For Cultural Arts Learning In Indonesian Traditional Music Materials - Haviana, Asani Gian; Sukmayadi, Yudi (Jurnal Seni Musik, 2021)
The development of science and technology is currently marked by the increasingly advanced field of Technology and Communication (ICT) in various sectors of life, including education. The use of application-based media is widely used during a pandemic. The world of education does not escape the role of digital-based media, such as learning in schools. There are times when students feel bored. Seeing the boredom of students when studying, it is necessary to make an innovation to motivate students to increase their enthusiasm. The author has an idea to create a music application. The purpose of this research is to make it easy for users or teachers and students to understand the material, especially Indonesian traditional music. The method used is Research and Development method and use the waterfall model, which is a systematic and sequential information system development model. Waterfall has the following stages: a. Requirements analysis and definition, b. System and software design, c. Implementation and unit testing, d. Integration and system testing, e. Operations and maintenance. The Mutranesia application is designed to support cultural arts learning in Indonesian traditional music materials. This app has six page views. First, the splash screen display. Second, display the Welcome page. Third, display the about page. Fourth, display the credits page. Fifth, map pages, and sixth, content display. The Mutranesia application is an android-based music application which has the concept of maps. The Mutranesia application is designed to support cultural arts learning in Indonesian traditional music materials. This app has six page views. First, the splash screen display. Second, display the Welcome page. Third, display the about page. Fourth, display the credits page. Fifth, map pages, and sixth, content display. The Mutranesia application is an android-based music application which has the concept of maps. The Mutranesia application is designed to support cultural arts learning in Indonesian traditional music materials. This app has six page views. First, the splash screen display. Second, display the Welcome page. Third, display the about page. Fourth, display the credits page. Fifth, map pages, and sixth, content display. The Mutranesia application is an android-based music application which has the concept of maps.